2011
DOI: 10.1002/app.33560
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SiO2 porosity on activity profiles and comonomer incorporation in slurry ethylene/butene‐1 polymerization by (SiO2/MgCl2/TEOS/TiCl4) catalyst system

Abstract: To investigate the influence of support porosity parameters e.g., average pore volume (APV), pore diameter (PD), and pore surface area distribution (PSAD) on activity-profile of catalyst and comonomer incorporation, a series of silica-supports with different porosity were prepared through sol-gel method and used to synthesize corresponding (SiO 2 /MgCl 2 /TEOS/TiCl 4 ) catalysts. Polymerization of ethylene/butene-1 showed that increasing of APV from 0.75 to 2.2 cm 3 g À1 SiO2 increase initial activity from 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, they also proposed that as the 1‐hexene concentration increased, a bulk convection effect led to its accumulation in the particles, and since it has a lower reactivity than ethylene, this in turn led to an overall lower reaction rate. Vakili et al also observed that silica particles with larger pores (and thus an increased friability) also gave a stronger comonomer effect in slurry copolymerization of 1‐butene and ethylene.…”
Section: Introductionmentioning
confidence: 96%
“…However, they also proposed that as the 1‐hexene concentration increased, a bulk convection effect led to its accumulation in the particles, and since it has a lower reactivity than ethylene, this in turn led to an overall lower reaction rate. Vakili et al also observed that silica particles with larger pores (and thus an increased friability) also gave a stronger comonomer effect in slurry copolymerization of 1‐butene and ethylene.…”
Section: Introductionmentioning
confidence: 96%